Adolescentes com limitações : estudo dos fatores associados às expectativas futuras - Canha, Lúcia (2019)
The transition from adolescent to life after high school is a particularly critical phase for the adolescent with limitations. The study of the factors that contribute to a successful transition is very important. Participants in this study were 76 students from the HBSC study, with several types of limitations. They had a mean age of 15.4 years (SD = 1.7) and 60% were female. They answered a set of questions related to the expectations and attitudes towards the future, perception of parent support, life satisfaction, future plans, objectives setting and perception of academic capacity. Family support factors, perceived academic ability, and attitudes toward the future predict 33% of variation in future expectations. The planning and definition of future goals are positively related to the sense of self-efficacy to deal with the professional future and the support of the family, regardless school achievement or general expectation of the future. Parental support seems to play a central role through the significant connections that this factor presents with future expectations, perception of academic ability and satisfaction with life. In order to develop a positive and proactive attitude towards the future, it is important that adolescents with disabilities experience their own experiences in the community - professional, social, recreational or voluntary work - that develop a sense of personal mastery. It is suggested that in the school, some of the interventions designed to promote the students’ capacitation for the transition after high school, be directed to the class. Technicians and teachers should be aware of the importance and potential of working in partnership with parents.